2015
DOI: 10.7326/m14-2358
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Allowing Choice of Diet on Weight Loss

Abstract: Correspondence and reprint requests: William S. Yancy, Jr. MD, VA Medical Center (152), 508 Fulton Street, Durham, NC 27705. Tel: 011-1-919-286-6936. Fax: 011-1-919-416-5836. yancy006@mc Publisher's Disclaimer: This is the prepublication, author-produced version of a manuscript accepted for publication in Annals of Internal Medicine. This version does not include post-acceptance editing and formatting. The American College of Physicians, the publisher of Annals of Internal Medicine, is not responsible for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 41 publications
(33 reference statements)
3
46
0
Order By: Relevance
“…The majority of patients who did not complete the assessment were lost to follow-up. See the primary outcomes paper for additional details on participant retention (Yancy et al, 2015). The average age of participants was 54.7 years old, and 73% were male.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of patients who did not complete the assessment were lost to follow-up. See the primary outcomes paper for additional details on participant retention (Yancy et al, 2015). The average age of participants was 54.7 years old, and 73% were male.…”
Section: Resultsmentioning
confidence: 99%
“…Details of the study design, procedures and intervention have been reported (Yancy et al 2015). Study participants were recruited from the Durham Veterans Affairs (VA) Medical Center between June 2011 and June 2012 via advertisements posted in clinic and hospital areas and referrals by VA health care personnel.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The weight loss program was an abbreviated version of a previous protocol that focused on calorie and fat restriction (16). It included education and strategies for behavior initiation as outlined in our theoretical model, including goal setting and self-monitoring of dietary intake and physical activity.…”
Section: Methodsmentioning
confidence: 99%